Credit Policy and Loan Recovery in Microfinance Institutions: A Case Study of Mubuga SACCO Kisoro District. - Murekatete, Rebecca (Kabale University, 2025)
The study assessed the effect of credit policy on loan recovery in microfinance institutions. A case study of Mubuga SACCO Kisoro district. The study was guided by three objectives, which were: to establish credit policies applied by Mubuga SACCO Kisoro district; to find out challenges impacting Mubuga SACCO Kisoro district; and to establish the relationship between credit policy and loan recovery at Mubuga SACCO Kisoro district. A targeted population of 40 respondents was considered for the study. These included top management, cashiers, loan officers, and accountants. Both simple random and purposive sampling techniques were used to identify the study sample size. The methods that were used in data collection included questionnaires. The collected data was edited, coded, entered into a computer, and analyzed with Excel, a Microsoft statistical package. The results were presented in tables. Based on the results of the study, 100% of the respondents agreed that there are various credit policies applied by Mubuga SACCO, and these include credit terms that involve both the length of the credit period and the discount rate, the loan amount recommended by the credit officer, and collateral security. The study findings revealed the challenges impacting Mubuga SACCO in credit policy and loan recovery in microfinance institutions: arrears rate, failure of appraisal of customers were common, loan appraisal policies were not clear, and there was existing collateral security that was inadequate. From objective three, it was found out, as indicated by the respondents from Mubuga SACCO, that there is a relationship between credit policies and loan recovery, and if good credit provides the institution with reasonable and adequate returns on loans, borrowers are given a small amount of money. The researcher concluded that there were various credit policies applied at Mubuga SACCO. The majority of the respondents reported that credit terms involved both the length of the credit period and the discount rate given, offering a uniform interest rate. The study findings further recommend that Mubuga SACCO should redesign its credit policy so as to make credit more effective to reduce loan losses and write-offs.